Diabetes and Tooth Loss in a National Sample of Dentate Adults Reporting Annual Dental Visits - Julie M. Kapp, PhD, MPH; Suzanne Austin Boren, PhD; Shumei Yun, PhD; Joseph LeMaster, MD, MPH (Centers for Disease Control and Prevention, 2007)
IntroductionPeriodontal disease has been associated with tooth loss and reported as more prevalent among people with diabetes than among those without diabetes. Having an annual dental examination is a national goal of Healthy People 2010. Our objective was to examine whether an association exists between diabetes and tooth loss among a population reporting an annual dental visit.MethodsWe used data from the 2004 Behavioral Risk Factor Surveillance System to examine the association between self-reported diabetes and tooth removal due to decay or periodontal disease among 155,280 respondents reporting a dental visit within the past year. We calculated prevalence estimates, odds ratios, and 95% confidence intervals. Multiple logistic regression allowed for adjustment.ResultsThe overall prevalence of tooth removal among the people in the study was 38.3%. People with diabetes had a significantly higher prevalence of tooth removal. In a multivariable model adjusting for selected covariates, respondents with diabetes were 1.46 times as likely (95% CI, 1.30-1.64) to have at least one tooth removed than respondents without diabetes. A stronger association between diabetes and tooth loss was observed among people in the younger age groups than among those in the older age groups.ConclusionEven among people reporting a recent dental visit, diabetes was independently associated with tooth loss. Multidisciplinary efforts are needed to raise awareness of the risk of tooth loss among younger people with diabetes. Good oral hygiene as well as annual dental examinations are important for preventing tooth loss.